4CPS-145 Pharmacogenetics as a tool in dose adjustment of immunosuppressive drugs: a case report. (March 2019) - Debailleul, M; Henry, H; Lepeut, G; Hennart, B; Decaudin, B; Mathurin, P; Odou, P
Abstract : Background: Tacrolimus is an immunosuppressant used after transplantation. Therapeutic drug monitoring is strongly recommended for this drug, because of its narrow therapeutic margin, interpatient variability, drug interactions and toxicity depending on concentration. Purpose: We report the case of a transplant patient who did not achieve the target residual concentration (Cres) of tacrolimus. Material and methods: The 64-year-old patient (130 kg–187 cm), had a liver transplant as treatment for alcohol-induced cirrhosis complicated by ascites, hepatic encephalopathy and esophageal varices with severe portal hypertension. A triple immunosuppression with mycophenolate mofetil, prednisolone and tacrolimus (Cres target=10–15 ng/mL) was initiated. Identification of Candida albicans in peri-operative collection and Enterobacter cloacae in blood culture required treatment by caspofungin and meropenem. Despite tacrolimus dose adjustment, Cres was not reached. Several hypotheses have thereby been explored: noncompliance, inappropriate sampling times, drug interactions and pharmacogenetics. A literature review was conducted, including the following keywords: tacrolimus, caspofungin, meropenem, interactions, pharmacogenetics. Results: Despite the gradual increase in tacrolimus dosage up to 15 mg per day (0.12 mg/kg/day), Cres obtained was below the therapeutic concentration target, reaching a maximum of 7.5 ng/mL in 8 days, and then decreasing to 3.7 ng/mL in 4 days. After investigation, noncompliance and sampling problems were excluded. Concerning drug interactions, the literature reported an increase in tacrolimus Cres when ertapenem (antibiotic from the same class as meropenem) was co-administrated: consequently meropenem was excluded from the hypotheses. With caspofungin, a decrease in tacrolimus Cres was described during a 10 day co-administration. However, this hypothesis seemed insufficient to explain the very important decrease in Cres. Concerning pharmacogenetics, the research found a need for higher doses of tacrolimus in patients carrying the CYP3A5*3 allele (from 0.15–0.25 mg/kg/day depending on genotype). This patient was found to be a heterozygous carrier of the g.6986A>G mutation, characteristic of the nonfunctional allele CYP3A5*3 . Due to the persistence of Cres low values, tacrolimus was finally replaced by cyclosporine. Conclusion: Pharmacogenetics may explain some resistance-to-treatment occurence, so it is important to raise awareness in the healthcare teams. Characterisation of the cytochrome 3A5 genotype can be a predictive means of tacrolimus dose optimisation, permitting the achievement of effective Cres while avoiding toxic effects. References and/or acknowledgements: No conflict of interest.